PERSPEKTIF ALLAMAH TABATABA’I TENTANG TEORI PERSATUAN DALAM FILSAFAT AGAMA - Babai, Habibullah; Nur, Sultan (Kanz Philosophia A Journal for Islamic Philosophy and Mysticism, 2013)
This paper discusses the theory of unity in religion, according to aphilosopher and mufassir, Allamah Tabataba’i. Though the discussion in this paper is about a social union, it is diff erent from the social justice. Unity described and presented in this section is included every form of unity within the various dimensions of society and certainly had a role and impact in shaping the social unity. Unity is also seen from the dimensions of the universal beliefs of individuals and the cosmological nature of society, as what the purpose and the meaning of religion itself that is to give stability to the social community in which to live their lives will also provide stability to the lives of individuals. The most important of which is the objective dimension where he directs the whole field and the social dimension in one direction, put it all on the line so that one of the individuals themselves and are led to a component of the community and to a social purpose. This purpose in view is none other Islamic monotheism and divine knowledge or ma’rifa.